2023
DOI: 10.1002/cbdv.202200969
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Inflammatory and Neuroprotective Effects of Standardized Fractions in Herniarin and Daphnoretin from Distictis buccinatoria

Abstract: Distictis buccinatoria is used for inflammatory‐related diseases. From a dichloromethane extract were obtained five different fractions called F1 to F5, and sub‐fractions F4‐1, F5‐1, F5‐2, and F5‐3; and were evaluated as anti‐neuroinflammatory, antioxidant, and nootropic agents in mice exposed to lipopolysaccharide. Also, were isolated herniarin, daphnoretin, and fraction's terpenes with an anti‐inflammatory activity using 12‐O‐tetradecanoylphorbol‐13‐acetate‐induced auricular edema. The inhibition of local ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Hernianin, or 7-methoxycoumarin, was found in substantial amounts in the fruits [11] . It has been found to have cytotoxic and anti-inflammatory activities [33,34] .…”
Section: Other Secondary Metabolitesmentioning
confidence: 99%
“…Hernianin, or 7-methoxycoumarin, was found in substantial amounts in the fruits [11] . It has been found to have cytotoxic and anti-inflammatory activities [33,34] .…”
Section: Other Secondary Metabolitesmentioning
confidence: 99%
“…Recent research has shown that different extracts of T. lucida have properties such as anti-inflammatory and antioxidant activities and mainly have a potential use against illnesses related to the CNS, providing antinociceptive and sedative effects, and treatment for disorders of depression and anxiety [17][18][19]21,23,[25][26][27][28][29]. The HPLC analysis of the TlHx and TlAcOEt extracts allowed the identification of five coumarins with biological activity: IC, HN, DF, SC, and PE.…”
Section: Quantification and Chemical Identification Of Five Coumarinsmentioning
confidence: 99%